Megatrends and weak signals shaping future real estate - Saija Toivonen (Buildings & Cities)
Society prepares for an envisioned future by shaping that future to align with current perceptions. This paper explores real estate market participants’ (n ≥ 840) perceptions of various forces influencing the future of housing, retail and office spaces, and their market environments. Real estate actors impact future cities through their space-use preferences, investment decisions and public regulations, which are driven by their expectations for the future. An environmental scanning method is used to investigate both megatrends and possible weak signals in Eastern Europe. The findings suggest that digitalisation and environmental pressure are perceived as the primary drivers of future spaces, while demographic forces play a lesser role. Although location and accessibility-related issues, along with economic drivers, have traditionally been paramount, these are now being overshadowed by the new forces. Sustainability is perceived to have a comparatively limited influence on office spaces compared with its impact on retail and housing. Technological development and digital transformation seem to eclipse the sector’s attention to demographic factors and sustainability concerns. Weak signals potentially driving the future development include emerging phenomena such as multicultural and generational space use, the role of urban nature, and innovations in the built environment. Practice relevance The findings provide insights into the perceptions of forces driving development action in cities related to housing, office and retail spaces. The results indicate that megatrends, digitalisation (particularly hybrid working) and environmental pressures (e.g. climate risks and regulatory changes) are widely recognised as dominant influences shaping how market actors prepare for the future. The results raise concerns about whether urban futures are being approached too narrowly, lacking a holistic understanding of the diverse drivers and possibilities ahead. These findings can inform real estate owners, developers and public sector stakeholders when developing futures-oriented processes and strategies. The findings can also reveal future space-use preferences for different types of spaces and indicate that real estate market actors prefer a long-term time horizon in real estate-related decisions contradicting many current practices.